TV drama in China - Zhu, Ying, 1965-; Keane, Michael, 1952-; Bai, Ruoyun, Ph. D. (TransAsia--screen cultures., 2008)
This collection of essays brings together the first comprehensive study of TV drama in China. It is organised into four sections: 'Tradition, History, and Politics', 'Gender and Domestic Sphere', 'Production, Reception, and Distribution' and 'Co-productions and Pan-Asian Markets'.